Analysis of The Influence of Maintenance and Service Quality on Baggage Handling System Performance Mediated by Stakeholder Satisfaction at Terminal 3 Soekarno-Hatta International Airport - Adek Rafles; Elsa Ratna Sari (Dinasti Review, 2025)
The growing number of passengers and the increasing volume of baggage require the baggage handling system at Terminal 3 Soekarno-Hatta International Airport to consistently operate at an optimal level and remain readily available at all times. This study aims to examine the influence of maintenance and service quality on system performance, mediated by stakeholder satisfaction with the baggage handling system facilities at Terminal 3 Soekarno-Hatta International Airport. A quantitative approach was employed, utilizing a survey method involving 100 respondents who represent the system’s stakeholders. Data analysis was conducted using a structural model approach through Partial Least Squares (SEM-PLS). The findings of the study indicate that maintenance and service quality exert a direct positive influence on system performance and stakeholder satisfaction, and an indirect positive influence on system performance mediated by stakeholder satisfaction. This study found that service quality has a positive effect on stakeholder satisfaction, which is the most dominant statement in the direct influence analysis with a t-statistic value of 3.913. The lowest statement of direct influence is maintenance on system performance with a t-statistic value of 3.156. The most dominant indirect influence statement is maintenance on system performance through stakeholder satisfaction with a t-statistic value of 2.373. System maintenance that is carried out in a timely, preventive and responsive can enhance stakeholder trust and comfort in the system. The higher the quality of maintenance and services provided, the higher the level of stakeholder satisfaction.